Czarty, kozły, zołzy i czarownice. Odczytanie powieści Salamandra Stefana Grabińskiego w kontekście Nocy Kupały - Wdowczyk, Anna (Kultura-Społeczeństwo-Edukacja, 2025)
The paper focuses on the motifs of Kupala Night and the character of the witch present in the novel Salamandra by Stefan Grabiński. For this reason, it undertakes an analysis of the beliefs, legends and superstitions used by the author concerning both the cult of the given holiday and the accompanying witches’ sabbaths. At the same time, the author wants to present the symbolism of the summer solstice, which is so important for this work, and also to discuss the sources from which the writer drew when creating the character of the titular witch. The aim of this paper is therefore to present the image of St. John’s Night preserved in cultural memory as a time of increased activity of supernatural beings and to discuss the literary evidence of the motifs of Kupala Night and the witch in the novel by one of the most valued fantasy authors of the interwar period.